2009
DOI: 10.17221/2843-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Furan in food - a review

Abstract: Furan and its derivatives were identified in a small number of heat-treated foods back in the 60's and 70's. In May 2004, US Food and Drug Administration published a report on the occurrence of parent furan in a number of thermally treated foods. Since furan has been classified as "possibly carcinogenic to human" by IARC, a great concern has been addressed to the analysis of this substance naturally-occurring in food. This paper gives a short overview on the mechanistic pathways of the parent furan formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 29 publications
1
58
0
3
Order By: Relevance
“…One calculation indicates that baby food consumption could result in a daily exposure as high as 3.5 g/kg for an infant (Vranová and Ciesarová, 2009). Others have calculated the mean infant food-derived furan exposure as ϳ0.4 g/kg per day with the 90th percentile being 1 g/kg per day and the mean adult food-derived furan exposure at ϳ0.3 g/kg per day with the 90th percentile predicted to be 0.6 g/kg per day (the U.S. Food and Drug Administration, Exploratory Data on Furan in Food: Individual Food Products, http://www.fda.gov/Food/FoodSafety/FoodContaminantsAdulteration/ ChemicalContaminants/Furan/ucm078439.htm, 2009).…”
Section: Food and Drug Administration Exploratory Data On Furan In Fmentioning
confidence: 99%
“…One calculation indicates that baby food consumption could result in a daily exposure as high as 3.5 g/kg for an infant (Vranová and Ciesarová, 2009). Others have calculated the mean infant food-derived furan exposure as ϳ0.4 g/kg per day with the 90th percentile being 1 g/kg per day and the mean adult food-derived furan exposure at ϳ0.3 g/kg per day with the 90th percentile predicted to be 0.6 g/kg per day (the U.S. Food and Drug Administration, Exploratory Data on Furan in Food: Individual Food Products, http://www.fda.gov/Food/FoodSafety/FoodContaminantsAdulteration/ ChemicalContaminants/Furan/ucm078439.htm, 2009).…”
Section: Food and Drug Administration Exploratory Data On Furan In Fmentioning
confidence: 99%
“…The chain of complex, competitive and consecutive reactions and the fact that they take place simultaneously generating many reactive intermediates make their interpretation and control difficult [Richardson, 2001]. Furan and many of its derivatives are one of the compound classes that can be found at very low levels in many foods and drinks as a result of thermal treatment [Vranová & Ciesarová, 2009]. The processes characterised by intensive thermal treatment are baking, toasting and roasting.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of foods which contain furan suggests that multiple pathways are likely to be involved in the formation of furan in foods (Morehouse et al 2007;Owczarek-Fendor et al 2011;. Studies performed in model systems have shown that furan and methylfuran can be generated from heating ascorbic acid, polyunsaturated fatty acids, unsaturated aldehydes, sugars, and amino acids (Perez & Yalayan 2004;Becalski & Slaman 2005;Limacher et al 2007;Limacher 2008;Roberts et al 2008;Vranová & Ciesarová 2009;Owczarek-Fendor et al 2010a,b, 2012Adams et al 2011;Duan & Barringer 2012;Anese & Suman 2013).…”
mentioning
confidence: 99%